MODAL SOSIAL PEDAGANG KELILING DI KELURAHAN PEBATUAN KOTA PEKANBARU - Rotua Fransiska Simanungkalit; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted on traveling traders in Kelurahan Pebatuan, Pekanbaru City with the aim of knowing how social capital and contributions become traveling traders for the family economy. This research uses descriptive qualitative research methods. The subjects in this study were 6 people. The technique for determining informants is to use techniques purposive sampling. Purposive sampling is taking the subject by specifying special characteristics in accordance with the objectives of the study so that it is expected to answer the research problem.In collecting data, researchers used observation, interview and documentation techniques. The theory used is the theory of social capital consisting of social networks, social norms and beliefs. The results of this study are that social capital is very important in running a mobile and smooth trading business such as networks that can help to expedite their businesses. Social norms that become a benchmark and make them more directed. Trust that makes it easy for them to buy goods to suppliers and in the transaction process with customers. With the existence of social capital such as networks, norms and beliefs it makes it easier for their businesses because in managing the business they are carried out together and a sense of trust is established. While being a traveling merchant, there is income that is used as a contribution to the family economy. The contribution is in the form of results which are used for daily needs. Keywords: Social Capital, Travelling Traders